2018
DOI: 10.1016/j.chb.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural study of Problematic Internet Use in nine European countries

Abstract: Reply to reviewersReviewer #1 Comment 1: The aim of the study was to investigate the relationships between Problematic Internet Use (PIU) and time spent online, online activities and psychopathology, by taking cross-cultural and gender differences into account. Additionaly it was aimed to explore the prevalence of PIU among European Internet users according the 5593 responding internet users. The topic is timely and interesting.It is not clearly explained if problematic gaming, gambling and pornography are sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
67
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 49 publications
15
67
4
2
Order By: Relevance
“…A study conducted in six Asian countries using IAT with a cutoff score of 70 on the IAT reported the following prevalence rates: South Korea (14%), China (19%), Hong Kong (35%), Malaysia (37.5%), Japan (48%), and Philippines (51%) (Mak et al 2014), whereas 14 to 55% was suggested as problematic use in nine European countries (Laconi et al 2018). A study of There may be several reasons explaining why no one in the present study was classed as being addicted to the internet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in six Asian countries using IAT with a cutoff score of 70 on the IAT reported the following prevalence rates: South Korea (14%), China (19%), Hong Kong (35%), Malaysia (37.5%), Japan (48%), and Philippines (51%) (Mak et al 2014), whereas 14 to 55% was suggested as problematic use in nine European countries (Laconi et al 2018). A study of There may be several reasons explaining why no one in the present study was classed as being addicted to the internet.…”
Section: Discussionmentioning
confidence: 99%
“…IA has been considered to be a public health problem (Bener and Bhugra 2013) and has been studied more in developed and developing countries. In a European study including nine countries, the prevalence rate of problematic internet use ranged between 14 and 55% (Laconi et al 2018). A study comprising six Asian countries found that the prevalence rate of IA using IAT with a cutoff score of ≥ 70 ranged between 14 and 51% (Mak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When predictor variables have been examined for problematic internet use, findings have also been consistent. In the majority of studies, depressive [1,14,10,12,13,5,15] and obsessivecompulsive symptoms [8,1,9,14,13,4,15] have been found to be the most significant predictors of problematic internet use.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most empirical studies have found a positive association between problematic internet use (PIU) and psychopathological symptoms both in normal samples of adolescents [1][2][3][4][5] and adults [6][7][8][9][10][11]. A few studies have examined this relationship among clinical samples (i.e., among diagnosed internet addicts), comparing them to healthy control groups [2,12,13] or clinical control groups [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation